Linking Human Resource Management to Pharmaceutical Supply Chain Performance: A Case Study of Drug Distribution in Remote Public Health Systems - Tien Trifeni; Kristian Hoegh Pride Lambe; Agustinus Agustinus; Putri Tianda Lambe (Management Study Program, Universitas Kristen Indonesia Paulus, 2026)
This study aims to analyze the role of human resource management (HRM) in supporting the effectiveness of drug distribution at the Pharmaceutical Warehouse of the P2KB Health Office in Central Papua Province. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, observations, and document analysis involving seven key informants, and analyzed using thematic analysis with source and method triangulation. The findings reveal that HRM practices have been implemented functionally but remain suboptimal, particularly in terms of workforce adequacy, workload distribution, and continuous competency development. Human resource competencies and experience contribute significantly to stock accuracy and timely drug distribution. However, geographical constraints, limited infrastructure, and an underdeveloped performance evaluation system hinder the consistency of distribution effectiveness. This study recommends strengthening competency-based HR planning, enhancing technical training in pharmaceutical logistics, and developing a more structured performance evaluation and motivation system to improve drug distribution performance, especially in geographically challenging regions.